2021
DOI: 10.46876/ja.938170
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition of Salvia officinalis and Rosmarinus officinalis

Abstract: Secondary metabolites, especially essential oils are of the widely used phyto-chemicals for various purposes. In this regard, numerous studies have been reported on profile of these reputed metabolites in medicinal and aromatic plant (MAPs) species. Of the substantial family of the MAPs, Lamiaceae is of the reputed group with a notable number of plant species. Regarding the species of this group, sage (Salvia officinalis) and rosemary (Rosmarinus officinalis) are of the well-known and widely-studied species. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…Another study reported similar chemicals to rosemary oil in our results (Mossa et al, 2019) which published that the main materials of rosemary oil are 31.45% 1,8-cineole, 8.8611% borneol, 1.01% alphapinene, 8.86% linalool, 7.32% camphor, 3.37% linalyl acetate, 3.32% alpha-terpineol, 3.42% Y-Terpinene and 1.82% Cymene. In addition, our findings regarding the components of rosemary oil were consistent with (Kocak et al, 2021). The essential oil product and its ingredients change as a result of growing conditions and environmental factors (Kulak et al, 2019).…”
Section: Resultssupporting
confidence: 79%
“…Another study reported similar chemicals to rosemary oil in our results (Mossa et al, 2019) which published that the main materials of rosemary oil are 31.45% 1,8-cineole, 8.8611% borneol, 1.01% alphapinene, 8.86% linalool, 7.32% camphor, 3.37% linalyl acetate, 3.32% alpha-terpineol, 3.42% Y-Terpinene and 1.82% Cymene. In addition, our findings regarding the components of rosemary oil were consistent with (Kocak et al, 2021). The essential oil product and its ingredients change as a result of growing conditions and environmental factors (Kulak et al, 2019).…”
Section: Resultssupporting
confidence: 79%